Genetic Mapping of Quantitative Trait Loci for Yield-Affecting Traits in a Barley Doubled Haploid Population Derived from Clipper × Sahara 3771 - Vafadar Shamasbi, Fatemeh; Jamali, Seyed Hossein; Sadeghzadeh, Behzad; Abdollahi Mandoulakani, Babak (Frontiers in Plant Science, 2017)
Many traits play essential roles in determining crop yield. Wide variation for morphological traits exists in Hordeum vulgare L., but the genetic basis of this morphological variation is largely unknown. To understand genetic basis controlling morphological traits affecting yield, a doubled haploid (DH) population (146 individuals) derived from Clipper × Sahar was used to map chromosome regions underlying plant heading date, plant height, fertile spike number, flag leaf length, spike length, harvest index, seed number per plant, thousands kernel weight and grain yield. Twenty-seven QTLs were mapped to the barley genome that described 3-69% of phenotypic variations. All mapped QTLs are novel in this study except one QTL flanked by VRS1 and KSUF15 markers. Chromosomal regions on 1H, 2H, 4H and 6H associated with seed grain yield, and chromosome regions on 2H and 6H had major effects on grain yield. One major QTL was found for seed number per plant that flanked by marker VRS1-KSUF15 on chromosome 2H. This QTL was also associated with grain yield (GY). Some loci controlling thousands kernel weight (TKW), fertile spike number (FSN), grain yield (GY) might be the same. The major grain yield QTL detected on linkage PSR167 co-localized with TAM10. Two major QTLs, controlling thousands kernel weight (TKW) and fertile spike number (FSN), were also mapped at this locus. Eight QTLs on chromosomes 1H, 2H, 3H, 4H, 5H, 6H and 7H consistently affected spike characteristics. One major QTL (ANIONT1A-TACMD) found on chromosome 4H that affected both spike length and spike number explained 9% and 5% of the variation of spike length and fertile spike number, respectively. It can be concluded that the identified markers with major effects such as VRS1-KSUF15 and PSR167-TMA10 could be efficiently used for marker assisted selection (MAS) in barley breeding programs.